ANALYSIS OF CONSUMER ATTITUDE AND TRUST ON THE PURCHASE INTENTION TO BUY HALAL COSMETICS IN BATAM - Suyono Saputra; Noviani Noviani (Universitas Internasional Batam, 2022)
This study aims to determine the behavior and consumer confidence in the intention to buy halal cosmetics in Batam City. The research method used is quantitative method. The variables in this study are Religiosity, Brand Image, Trust and Attitude and Purchase Intention. The technique used in this research is purposive sampling. The object of research is consumers who have bought halal cosmetics in Batam City by distributing questionnaires via google form. The sample data used according to Hair et al., (2010) is the 1:10 technique. The data that has been collected by the researchers are 349 respondents. The data processed by the researcher is using the Smart PLS application. After this research was conducted, it can be concluded that Religiosity has a significant positive effect on Attitude, Brand Image has a significant positive effect on Attitude, Brand Image has a significant positive effect on Trust, Brand Image has a significant positive effect on Purchase Intention. Attitude has a significant positive effect on Purchase Intention, and Trust has a significant effect on Purchase Intention